Cancer patients' behaviors and attitudes toward natural health products - Audrey Schils; Anne-Sophie Lechon; Sarah Rondeaux; Florence Souard; Jean-Luc Van Laethem; Stephanie Pochet; Veronique Mathieu; Carine De Vriese (BMC, 2023)
Abstract Background Natural health products (NHPs), including vitamins, minerals, and herbal supplements, are the most common complementary and alternative medicine (CAM) among cancer patients. Our survey determined the attitudes and behaviors of cancer patients toward natural complementary therapies that should be considered to implement an integrative approach in the future. Methods Our survey was conducted in four hospitals in Belgium. Questionnaires were posted online from October 2020 to October 2021 for cancer patients. Descriptive statistics were used to analyze the data. A $$χ ^{2}$$ χ 2 test was applied to study the type of NHP consumed according to diagnosis time. Fischer's exact test compared patients who had changed their consumption since diagnosis and those who had not. Results Out of 349 questionnaires collected, only 59 met all inclusion criteria. 83.1 % of the patients agreed that conventional medicine (CM) could benefit from complementary therapies, but they did not estimate (72.3 % of the patients) that those latter are more effective than conventional medicine. More than half of the patients used five or more NHPs. The most frequent NHPs consumed daily were vitamins (64.4 %), followed by other products (i.e., probiotics, gemmotherapy, birch sap and omega 3/6) (42.4 %) and herbs (40.7 %). Almost all patients started taking NHPs before their cancer diagnosis, but 72.7 % have changed their consumption significantly (p = 0.009) since their diagnosis. Boosting the immune system (79.7 %) and limiting conventional treatment side effects (76.9 %) were the most common reasons for NHPs' use. 74.4 % of the patients did not take complementary therapies to delay or avoid conventional treatment. Conclusions The combination and high diversity of NHPs consumption highlight the importance of educating patients and healthcare providers (HCPs) about the risk of drug interactions associated with these natural products. Most cancer patients are more interested in using this non-mainstream medicine to complement their conventional treatment than as an alternative. Knowing the patients' reasons and understanding patients' attitudes toward NHPs will be essential for HCPs to address NHPs' use.